Pelayanan Pembuatan E-KTP Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Sigi - Devina, Adhe; Ardianti, Meri; Lufira, Lufira; Putri, Azmi Mardia; Nurhayati, Nurhayati; Mustainah, Mustainah; Kurnia, Intam; Haryono, Dandan; Borman, Mohammad Riski (PARADIGMA : Jurnal Administrasi Publik, 2025)
This study aims to evaluate the quality of services in issuing Electronic Identity Cards (e-KTP) at the Department of Population and Civil Registration of Sigi Regency based on the five dimensions of service quality in the SERVQUAL model: tangibles, reliability, responsiveness, assurance, and empathy. This research employs a qualitative approach with a descriptive type. Data were collected through observations, interviews, and documentation involving service officers and community members who were in the process of obtaining an e-KTP. Data analysis was conducted through data reduction, data presentation, and conclusion drawing using Miles and Huberman’s analytical technique. The results indicate that the quality of e-KTP services in Sigi Regency has not been fully optimal. In the tangibles dimension, service facilities are considered adequate; however, the waiting room is still narrow and uncomfortable, making it unable to accommodate the number of applicants during peak service hours. In the reliability dimension, services follow established procedures, but the stability of the Population Administration Information System (SIAK) network often experiences disruptions, slowing down the recording and printing processes of e-KTPs. In the responsiveness dimension, officers are deemed responsive and provide clear guidance to the public, although the speed of service completion is highly influenced by network conditions. In the assurance dimension, officers possess the necessary competence, behave politely, and are able to provide a sense of security through open and informative explanations of procedures. Meanwhile, in the empathy dimension, officers demonstrate a friendly attitude, are non-discriminatory, and provide attention to the needs of the community. The conclusion of this study shows that although officers have provided fairly good services, several aspects still need improvement, particularly regarding the enhancement of physical facilities and optimization of the SIAK network. More comprehensive improvement efforts are required so that e-KTP services in Sigi Regency can run more effectively, comfortably, and meet public service quality standards.